Study of indications of primary cesarean section in multigravida patients: A retrospective study - Meena, Nidhi; Parveen, Saba; Nagar, Teena; Naresh Kumar Meena, (Asian Journal of Medical Sciences, 2022)
Background: Caesarean section is one of the most widely performed surgical procedures in obstetrics worldwide. It was mainly evolved as a lifesaving procedure for mother and foetus during the difficult delivery. Multiparous means those who had delivered once or more after the age of viability. It includes multipara (para 2, 3, 4) and grand multipara (para more than 4). Primary Caesarean section in the multipara means first Caesarean section done in the patients who had delivered vaginally once or more. Aims and Objectives: The aims of this study were to study the indications for the primary cesarean section in multigravida women at tertiary care center, Medical College Jhalawar. Materials and Methods: Retrospective record-based study of all primary cesarean section in multigravida women admitted at Janana Hospital, Medical college Jhalawar during the period of 3 months. Retrospective analysis of case sheet was done in parous women who had previous vaginal deliveries. Inclusion criteria were all multigravida who went for the lower segment cesarean section (LSCS). Results: During the study period of 3 months, total 1968 deliveries occurred, out of which 806 (40.95%) underwent cesarean section and 208 (25.80%) among these cesarean sections were underwent primary cesarean section in multigravida. Maximum number of the patients were in the age group of 25–30 years 120 (57.69%). Maximum number of patients were gravida 2 (G2) 135 (63.67%) and gravida 3 (G3), 52 (24.52%). Almost all of them (96.63%) underwent emergency cesarean section. The most common indication for the primary LSCS in multigravida patients was fetal distress 46 (22.11%) followed by malpresentation 38 (18.26%) cases, meconium stained liquor with fetal distress 23 (11.05%), severe oligohydramnios 15 (7.21%), non-progress of labor 13 (6.25%), pre-eclampsia and big baby 8 (3.84%) each, elective CS with bad obstetric history, obstructed labor and placenta praevia 7 (3.36%) reach, APH and cephalopelvic disproportion 6 (2.28%) each, and PIH 5 (2.24%). Conclusion: The most common indication for the primary LSCS in multigravida patients was fetal distress 46 (22.11%) followed by malpresentation 38 (18.26%) cases in our study.